Ecological Engineering: A Potential Way for Controlling Pests and Improving Paddy Productivity - Saravanakumar, S. (Indian Journal of Extension Education, 2020)
Paddy (Oryza sativa L.) is an important food crop cultivated over 40,000 ha in Erode district. Attempts wereÂ made to control the pests in paddy by adopting recent techniques called Ecological Engineering. The technologies comprised of seed treatment with pseudomonas and azospirillum, growing of bund crops like sunflower, aster, urd, mung for attracting the natural enemies, installation of traps for monitoring the pest population, plant protection by using plant extracts and bio pesticides were demonstrated in the farmersâ€™ field. The resultsÂ showed that, adoption of ecological engineering methods reduced the pest infestation percentage to 9.75 per cent over compared practices of 23.12 per cent. The natural enemiesâ€™ population of 16.65 numbers was recorded in demonstrated plot/m2 and in farmersâ€™ practice on an average 2.6 natural enemies observed. The results showed that the higher grain yield of 4620 kg/ha compared to 4196.5 kg/ha in farmers practice with the yieldÂ advantage of 10.12 per cent. The average extension gap, technology gap and technology index were 423.5 kg/ ha, 480 kg/ha, and 9.41 per cent, respectively. The result reveals that the adoption of ecological engineering practices in paddy cultivation reduces the pest infestation and improves the productivity in an eco friendly manner.